Profiling Karakteristik Peserta Didik Sebagai Acuan Perencanaan Pembelajaran Berdiferensiasi di SMAN Mumbulsari Jember - Azrina, Nuril; Agus Prasetyo, Agus Prasetyo (Indonesian Journal Publisher, 2023)
A new paradigm of learning ensures that learning is centered around the learners. Educators are given the freedom to plan learning that accommodates the characteristics and needs of each learner. This accommodating activity can be carried out when educators already know and understand the characteristics of the learners themselves. However, in practice, the understanding of these learner characteristics has not been maximized. It becomes a concern if the understanding of learner characteristics is not done, as it will have an impact on optimizing the achievement of learning goals and the potential of the learners, as well as the meaningfulness of learning. The purpose of this research is to produce important data or information related to the profiling of the characteristics of the X-1 class students of SMA Negeri Mumbulsari, Jember, which can be used as a basis for optimizing learning activities. The characteristics examined are limited to the aspects of learning styles and student interests. Data is collected through observations and questionnaires for the students. Meanwhile, the research method used is qualitative research. The results of the research show that the X-1 class students at SMA Negeri Mumbulsari mostly have a lack of interest in the learning process, and the most dominant learning style among the students is visual learning.